Tadpoles of the endangered Ka Lon litter toad, Leptobrachella kalonensis (Anura: Megophryidae): molecular identification and morphological description - Le, Duong Thi Thuy; Tran, Thinh Gia; Pham, Manh Hung (Tropical Natural History, 2023)
Tadpole identification has important implications for subsequent studies on the life history, behavior, ecology, and distribution of amphibian species. The tadpole morphology of the Ka Lon litter toad, Leptobrachella kalonensis, is first characterized based on DNA barcoding identification. The description is based on the collection of four tadpoles at stage 26 from a disturbed stream in Di Linh plateau, central Vietnam. DNA sequences of the mitochondrial 16S rRNA gene obtained from the tadpoles have less than 0.2% sequence divergence with the adult L. kalonensis in GenBank, rendering the identification unambiguous. The tadpoles of this species were discovered in a small pool in a rocky cascade stream covered by a disturbed broadleaf and bamboo forest. Tadpoles of L. kalonensis are found to be distinguished from those of their congeners by having a significantly elongated body, a tail twice as long as the body, a uniform brown color without a distinct pattern, an intestinal tube that is invisible due to the robustness of the rectus abdominis muscle, and an LTRF 2(1–2)/2(1–2) or 2(1–2)/2(1). A previously unknown locality for this species on the Di Linh plateau is also reported, which further verifies the IUCN Redlist’s suggestions regarding the geographic range of the species.